PENINGKATAN HASIL BELAJAR SISWA PADA ELEMEN BHINNEKA TUNGGAL IKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS IV SDN 13 BATU GADANG KOTA PADANG - Putri, Lisa; Yesi Anita; Reinita; Etri Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the improvement of student learning outcomes on the elements of Bhinneka Tunggal Ika using the problem based learning model in class IV SDN 13 Batu Gadang, Padang City. This type of research is Classroom Action Research () using qualitative and quantitative approaches. This research was conducted in two cycles, cycle I with two meetings and cycle II with one meeting. The subjects of this study were teachers (researchers) and students totaling 28 students, 15 male students and 13 female students. The results of this study showed an increase in: 1) RPPM cycle I with an average of 85.41% (Good) and increased in cycle II with an average of 95.83% (Very Good). 2) Implementation of teacher activities cycle I averaged 81.54% (Good) and increased in cycle II 92.85% (Very Good). 3) Student assessments for improving learning outcomes in cycle I averaged 79.37% (Sufficient) and increased to 90.18% (Very Good) in cycle II.